The Association Between Family Knowledge and Support with the Readiness of Madrasah Ibtidaiyah Students in Facing Menarche - Putri Handayani; Christina R. Nayoan; Tanti Rahayu (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Menarche is a sign of a change in social status from child to adult. The importance of knowledge and family support influences female students' readiness to face menarche. Knowledge is related to the physiology and psychology of young women regarding menstruation, while family support is related to the role of parents. The unpreparedness of young women in facing menarche has an impact on their implementation in daily life and young women are more susceptible to reproductive tract infections. Objective: This study aims to analyze the relationship between knowledge and family support and female students' readiness to face menarche at Al-Fitrah Private Madrasah Ibtidaiyah, Kupang City. Method: This research was conducted in February 2024. The research design was analytical observational with a quantitative approach with a cross-sectional design. The population in this study were female students in grades IV, V, and VI at Al-Fitrah Private Madrasah Ibtidaiyah Kupang City, namely 52 respondents. The technique used in this research is proportional sampling. The instrument used was a questionnaire consisting of a readiness-to-face menarche questionnaire, a knowledge questionnaire, and a family support questionnaire. Data analysis used univariate analysis and bivariate analysis using the chi-square test. Result: Data analysis used univariate analysis and bivariate analysis using the chi-square test. The results of the research show that there is a relationship between knowledge and family support and the readiness of female students to face menarche at Al-Fitrah Private Madrasah Ibtidaiyah with a p-value of 0.015 and 0.025 (< 0.05). It is known that 33 out of 52 female students with poor or good knowledge and poor or good family support are ready to face menarche (63.5%). Meanwhile, 19 out of 52 were not ready to face menarche (36.5%). Conclusion: There is a relationship between knowledge and family support and female students' readiness to face menarche at Al-Fitrah Private Madrasah Ibtidaiyah, Kupang City